Recombinant expression and functional analysis of transgelin-like protein from the shell of Mytilus coruscus - JIANG Yuting; SUN Qi; XU Huanzhi; SHEN Wang; ZHANG Xiaolin; FAN Meihua; LIAO Zhi (浙江大学学报. 农业与生命科学版)
Transgelin-like protein (TLP) is a novel shell matrix protein identified previously from the myostracum layer of Mytilus coruscus shell. For exploring its function in the shell formation of mussel, the TLP was recombinantly expressed by Escherichia coli expression system based on the sequence analysis and codon optimization. The functions of recombinant TLP (rTLP) on calcite- and aragonite-type calcium carbonate crystals were then investigated, including morphology, polymorph, crystallization rate, and binding ability of calcium carbonate crystals. Sequence analysis showed that the TLP contained a calponin homology (CH) domain, and the spatial structure of TLP predicted by SWISS-MODEL presented a conformation formed predominately by α-helices. Functional analyses showed that the rTLP had significant effects on the morphological change of aragonite-type calcium carbonate crystal and polymorph change of calcite-type calcium carbonate crystal, suggesting the function of this protein in the transformation of calcite to aragonite. In addition, the rTLP showed inhibition of calcite-type calcium carbonate crystallization rate in vitro, and promotion of aragonite-type calcium carbonate crystallization rate under high protein concentration. Moreover, the rTLP presented binding abilities to the calcite-type calcium carbonate crystal rather than the aragonite-type calcium carbonate crystal. Considering the myostracum layer is composed of aragonite-type calcium carbonate crystal, we speculate that the TLP may play important roles in the shell biomineralization and the formation of myostracum layer.